2017
DOI: 10.1016/j.actatropica.2017.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Third record of Rhodnius amazonicus and comparative study with R. pictipes (Hemiptera, Reduviidae, Triatominae)

Abstract: Rhodnius amazonicus Almeida et al. (1973) is a triatomine of rare occurrence. This species was found for the third time in Breves city, Pará state, Brazil. Morphometric and morphological studies were carried out on one male and one female. Lent and Wygodzinsky (1979) considered this species as a synonym of R. pictipes, until its revalidation after 23 years by Bérenger and Pluot-Sigwalt (2002). Considering the synonym mentioned above, a comparative study between these two species was performed in order to repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…The occurrence of sylvatic species, like P. geniculatus, invading sporadically human dwellings, was noted by Caranha et al (2011) as a major difficulty for vector surveillance programs. On the other hand, insular records of triatomines, although unusual, have already been recorded in the literature (Sousa et al 1983;Rebelo et al 1998;Valente 1999;Sagua Franco et al 2000;Rosa et al 2017;). These records show the necessity of entomological surveys of isolated populations on islands.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The occurrence of sylvatic species, like P. geniculatus, invading sporadically human dwellings, was noted by Caranha et al (2011) as a major difficulty for vector surveillance programs. On the other hand, insular records of triatomines, although unusual, have already been recorded in the literature (Sousa et al 1983;Rebelo et al 1998;Valente 1999;Sagua Franco et al 2000;Rosa et al 2017;). These records show the necessity of entomological surveys of isolated populations on islands.…”
Section: Discussionmentioning
confidence: 86%
“…The blood-sucking insects of the subfamily Triatominae (Hemiptera, Heteroptera, Reduviidae) are vectors of Chagas disease, an infection caused by the flagellate protozoan Trypanosoma cruzi (Chagas, 1909). The subfamily is composed of 151 extant and three fossil species assigned to five tribes and 19 genera (Rosa et al 2017;Dorn et al 2018;Lima Cordon et al 2019;Poinar-Jr 2019). The genus Panstrongylus Berg, 1879 was described, based on P. guentheri Berg, 1879, and has 15 species, nine of them recorded in Brazil (Galvão 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In Triatominae, morphological structures of male genitalia have traditionally been extensively used for taxonomic purposes (Souza et al 2017, Oliveira et al 2018), whereas features of female genitalia have not been well explored. As a result of improvements in scanning electron microscopy (Rosa et al 2010, 2014), identification of details in female external genitalia demonstrated its utility for specific differentiation of this group.…”
Section: Discussionmentioning
confidence: 99%
“…For taxonomic purposes the tool was also applied to complement the description of Rhodnius montenegrensis (Rosa et al 2012), R. marabaensis (Souza et al 2016), R. taquarussuensis (Rosa et al 2017) and Nesotriatoma confusa (Oliveira et al 2018) and in the characterization of 35 species distributed in seven genera (Rosa et al 2012, 2017, De Oliveira et al 2015, Dos Santos Souza et al 2016, Mendonça et al 2016, Rivas et al 2017, Souza et al 2017, Rodrigues et al 2018). Here, the morphological study of the female external structures of the species of the T. brasiliensis complex was analyzed for the first time and provided a relevant contribution for the group.…”
Section: Discussionmentioning
confidence: 99%
“…Rhodnius neivai is found on fallen tree trunks and in the crowns of the llanera palm (Copernicia tectorium) in Colombia and Venezuela [47,56]. Rhodnius amazonicus and R. paraensis are distributed in French Guiana and Brazil, where R. paraensis has been found in nests of arboreal rodents of the genus Echimys [11,56,58]. Finally, R. zeledoni was identified in a single report in the northeast of Brazil in the state of Sergipe [72].…”
Section: Genus Group Speciesmentioning
confidence: 99%